IPR and Digital Space - Dr. Gaytri Devi; Vinny Sukija (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
In the digital age, intellectual property rights (IPR) play a crucial role in safeguarding innovation and creativity. The Intellectual Property Rights has a key role in nurturing research and inventions of every nation. These rights protect both individual and national interest through giving opportunity for economic growth. Always, the unique expression of ideas or products is being important in all commercial endeavors. In today’s digital world, there are more chances of stealing trade secrets or illegal use of registered properties, as the entire world is connected with networks. The loss of intellectual property can be harmful to a nation’s overall development, as it weakens the encouragement for innovation. To protect a nation’s intellectual wealth, issues related to IPR infringement must be addressed and handled effectively. This paper explores the digital landscape, the various types of IPR, and the diverse ways in which intellectual properties can be violated in the digital realm. It aims to shed light on the evolving role of IPR in safeguarding innovation and creativity in the digital age, while also highlighting the challenges and potential solutions for protecting intellectual property rights in the online world.